XML Certification Quizzer. - Amoussou, Joel
Last month's column introduced you to the exam objectives for IBM Test 141 on XML and Related Technologies. This installment will present five more questions from the five different exam objectives. It can be used as a learning tool for people who are new to XML. If you are preparing for the exam, the article will help you review key concepts.